Respuestas
Respuesta dada por:
17
Respuesta:
7x - 15y = 1
- x - 6y = 114
7x - 15y = 1
- 7(x) - 7(6y) = 7(114)
7x - 15y = 1
- 7x - 42y = 798
-----------------------
- 57y = 799
- 57y = 799
y = 799 / (- 57)
y = - 799 / 57
- x - 6y = 114
- x - 6(- 799 / 57) = 114
- x + 6(799 / 57) = 114
6(799 / 57) - 114 = x
(4794 - 57(114)) / 57 = x
(4794 - 6498) / 57 = x
- 1704 / 57 = x
x = - 1704 / 57
y = - 799 / 57
7x - 15y = 1
- x - 6y = 114
7x - 15y = 1
- 7(x) - 7(6y) = 7(114)
7x - 15y = 1
- 7x - 42y = 798
-----------------------
- 57y = 799
- 57y = 799
y = 799 / (- 57)
y = - 799 / 57
- x - 6y = 114
- x - 6(- 799 / 57) = 114
- x + 6(799 / 57) = 114
6(799 / 57) - 114 = x
(4794 - 57(114)) / 57 = x
(4794 - 6498) / 57 = x
- 1704 / 57 = x
x = - 1704 / 57
y = - 799 / 57
Respuesta dada por:
0
Respuesta:
no me ayudó nada más información
Preguntas similares
hace 6 años
hace 6 años
hace 9 años
hace 9 años